FAN1 interaction with ubiquitylated PCNA alleviates replication stress and preserves genomic integrity independently of BRCA2. Issue 1 (December 2017) - Porro, Antonio; Berti, Matteo; Pizzolato, Julia; Bologna, Serena; Kaden, Svenja; Saxer, Anja; Ma, Yue; Nagasawa, Kazuo; Sartori, Alessandro; Jiricny, Josef
Abstract Interstrand cross-link (ICL) hypersensitivity is a characteristic trait ofFanconi anemia (FA). Although FANCD2-associated nuclease 1 (FAN1) contributes to ICL repair, FAN1 mutations predispose to karyomegalic interstitial nephritis (KIN) and cancer rather than to FA. Thus, the biological role of FAN1 remains unclear. Because fork stalling in FAN1-deficient cells causes chromosomal instability, we reasoned that the key function of FAN1 might lie in the processing of halted replication forks. Here, we show that FAN1 contains a previously-uncharacterized PCNA interacting peptide (PIP) motif that, together with its ubiquitin-binding zinc finger (UBZ) domain, helps recruit FAN1 to ubiquitylated PCNA accumulated at stalled forks. This prevents replication fork collapse and controls their progression. Furthermore, we show that FAN1 preserves replication fork integrity by a mechanism that is distinct from BRCA2-dependent homologous recombination. Thus, targeting FAN1 activities and its interaction with ubiquitylated PCNA may offer therapeutic opportunities for treatment ofBRCA -deficient tumors. FANCD2-associated nuclease 1 (FAN1) is a key protein involved in the metabolism of DNA and in human pathologies. Here, the authors show that FAN1 directly interacts with PCNA at stalled replication forks to control their progression and prevent their collapse.